2007
DOI: 10.5194/acpd-7-15565-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dust aerosol radiative effect and influence on urban atmospheric boundary layer

Abstract: Abstract. An 1.5-level-closure and 3-D non-stationary atmospheric boundary layer (ABL) model and a radiation transfer model with the output of Weather Research and Forecast (WRF) Model and lidar AML-1 are employed to simulate the dust aerosol radiative effect and its influence on ABL in Beijing for the period of 23–26 January 2002 when a dust storm occurred. The simulation shows that daytime dust aerosol radiative effect heats up the ABL at the mean rate of about 0.68 K/h. The horizontal wind speed from ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For example, a 1.5 level closure and 3‐D nonstationary atmospheric boundary layer (ABL) model and a radiation transfer model driven by the output of Weather Research and Forecasting Model and lidar AML‐1 are employed to simulate the dust aerosol radiative effect and its influence on ABL for the period of 23–26 January 2002, when a dust storm occurred in Beijing. The result shows that dust aerosol radiative effect heats up the atmospheric boundary layer (ABL) by a mean rate of about 0.68 K/h during daytime but cools the ABL by −0.21 K/h during night [ Zhang et al ., ]. By using the Clouds and Earth's Radiant Energy System data and the Fu‐Liou radiative transfer model, the impact of Asian dust on cloud radiative forcing during 2003–2006 is studied.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 1.5 level closure and 3‐D nonstationary atmospheric boundary layer (ABL) model and a radiation transfer model driven by the output of Weather Research and Forecasting Model and lidar AML‐1 are employed to simulate the dust aerosol radiative effect and its influence on ABL for the period of 23–26 January 2002, when a dust storm occurred in Beijing. The result shows that dust aerosol radiative effect heats up the atmospheric boundary layer (ABL) by a mean rate of about 0.68 K/h during daytime but cools the ABL by −0.21 K/h during night [ Zhang et al ., ]. By using the Clouds and Earth's Radiant Energy System data and the Fu‐Liou radiative transfer model, the impact of Asian dust on cloud radiative forcing during 2003–2006 is studied.…”
Section: Introductionmentioning
confidence: 99%
“… Meloni et al [2005] found that SW aerosol radiative forcing at TOA is strongly dependent on aerosol vertical profiles. Substantial magnitude and large uncertainties were found for aerosol radiative forcing in some heavily polluted regions [ Li , 1998; Satheesh and Ramanathan , 2000; Huang et al , 2008c; Zhang et al , 2007]. Ramanathan et al [2001] suggested that a combination of the aerosol direct and indirect effects could weaken the hydrological cycle, which could be a major environmental issue during this century.…”
Section: Introductionmentioning
confidence: 99%
“…The dust aerosol severely affects the local climate and environment by influencing the atmospheric radiation balance and decreasing atmospheric visibility (Wang et al, 2005). Recent years have witnessed numerous studies on the aerosol radiative properties (Blanco et al, 2003;Gobbi et al, 2003;Immler et al, 2003;Collaud Coen et al, 2004;Papayannis et al, 2005;Balkanski et al, 2007;Zhang et al, 2007;Su et al, 2008;Hong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%